2015
DOI: 10.3846/20297955.2015.1113900
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of Sustainable Urban Development Indicator for the Montreal Urban Community

Abstract: The City of Montreal initiated a First Strategic Plan for Sustainable Development in 2005 followed by a Community and Corporate Sustainable Development Plan in 2010-2015. This study proposes a sustainable urban development indicator (SUDI) for each Montreal Urban Community (MUC) to evaluate the achievements of sustainable development plans. This study identifies thirty-two variables as the attributes of sustainable urban development. The multivariate technique and Exploratory Spatial Data Analysis are applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Complementing this concept set out by the World Commission on Environment and Development, the sustainability goals of a city are also planned to achieve the harmonious development of the urban economy, population, resources and environment; see Paper 3 (high-adherence class) [32]. This development of the urban economy can be seen in the studies reported by Pourshahabi et al [6], and Amin and Tamima [33], referring to the positive effects motivated by the efficient allocation of public resources, thus contributing to the literature on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Complementing this concept set out by the World Commission on Environment and Development, the sustainability goals of a city are also planned to achieve the harmonious development of the urban economy, population, resources and environment; see Paper 3 (high-adherence class) [32]. This development of the urban economy can be seen in the studies reported by Pourshahabi et al [6], and Amin and Tamima [33], referring to the positive effects motivated by the efficient allocation of public resources, thus contributing to the literature on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…A principal component analysis (PCA) was applied to estimate the values of D, COMV and STRINFV indices. The value of each index was calculated by multiplying the standardized value of the corresponding attributes (Figure 2), the proportion of variance explained by each attribute and the proportion of variance explained by each factor (under which that particular attribute is loaded) (Amin and Tamima, 2015). The standardized value of each attribute was used in order to remove the effect of different units of measurement and to warrant cross comparisons.…”
Section: Vulnerability Index =mentioning
confidence: 99%
“…was applied to estimate the D, COMV and STRINFV indices. The value of each index was calculated by multiplying the standardized value of the corresponding attributes (Figure 2), the proportion of variance explained by each attribute and the proportion of variance explained by each factor (under which that particular attribute is loaded) (Amin and Tamima 2015).…”
Section: Geophysical Risk and Vulnerability (Geophriv) Index Of Roadsmentioning
confidence: 99%